Pedagogical Games Used in Primary School Mother Tongue and Reading Literacy Classes (Grade 2 Example) - qizi, Sharifjonova Kamolaxon Tohirjon (European Journal of Life Safety and Stability (2660-9630), 2022)
The article discusses games used in mother tongue and teaching literacy classes.